1986
DOI: 10.1029/jc091ic11p12957
|View full text |Cite
|
Sign up to set email alerts
|

Space and time variability of the surface color field in the northern Adriatic Sea

Abstract: A time series of coastal zone color scanner images for the years 1979 and 1980 was used to observe the spatial and temporal variability of bio‐optical processes and circulation patterns of the northern Adriatic Sea on monthly, seasonal, and interannual scales. The chlorophyll‐like pigment concentrations derived from satellite data exhibited a high correlation with sea truth measurements performed during seven surveys in the summer of both years. Comparison of the mean pigment fields indicates a general increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 20 publications
3
31
0
Order By: Relevance
“…Evidence of filaments coming off this current can be found, especially in winter north of Ancona and at the tip of the Gargano peninsula. These observations are in agreement with previous work in the Adriatic using CZCS data (Barale et al, 1986(Barale et al, , 1984.…”
Section: Chlorophyll Concentrationssupporting
confidence: 83%
See 2 more Smart Citations
“…Evidence of filaments coming off this current can be found, especially in winter north of Ancona and at the tip of the Gargano peninsula. These observations are in agreement with previous work in the Adriatic using CZCS data (Barale et al, 1986(Barale et al, , 1984.…”
Section: Chlorophyll Concentrationssupporting
confidence: 83%
“…Estimates based on the Coastal Zone Color Scanner (CZCS) by Antoine et al (1995) confirm that the Adriatic Sea has the highest pigment biomass and primary production of all the Mediterranean sub-basins. Using CZCS data, Barale et al (1986) showed a direct correlation between the winter-spring pigment distributions in the northern Adriatic and the Po River freshwater discharge. Barale et al (1986) also noted that wintertime vertical mixing over the northern shelf could be important because of the co-occurrence of high pigment levels with meteorological conditions associated with dense water formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the concentration of chlorophyll-like pigments of phytoplankton or, more likely in this case, total suspended matter concentration) in the mapping of surface waters (from 0 to 10 m depth, Barale et al 1992). The data were corrected for atmospheric interference using the algorithms of Gordon & Clark (1981), Gordon et al (1983) and Barale et al (1986) and they represent a mean of all monthly composites for the period, at a resolution of 1 × 1 km. We processed the data using WinChips 4.1b and Idrisi for Windows 2.0, and applied a 3 × 3 mode filter to the data in order to obtain a more general picture.…”
Section: Methodsmentioning
confidence: 99%
“…1) is considerable, since they can contribute with lowsalinity patches that are relevant to mesoscale and submesoscale dynamics (Marini et al, 2008;Solidoro et al, 2009). These freshwater discharges and associated particulate and dissolved matter inputs have a significant effect, both on the physical and biogeochemical properties of the whole basin (Zavatarelli et al, 1998;Marini et al, 2008;Solidoro et al, 2009;Bignami et al, 2007;Barale et al, 1986;Tesi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%